Organizational management : case studies for graduate students - Bayeh, Ziad (Bentham Science Publishers, 2015)
This book presents two case studies of two organizations operating in Lebanon. The author has examined the organizational management practices of these two companies and then proposed solutions for each identified problem. The case studies represent an electromechanical company working in the construction field and a retail company that sells different product lines. This handbook is suitable for readers who are familiar with concepts in organizational management and development. Engineers working in the construction field may also find this book helpful in improving their managerial expertise and for understanding the way different departments within a company work together.